Numerical Simulations of Drag-Reducing Devices for Ground Vehicles - Mazyan, Walid Ibrahim (2013)
A Master of Science thesis in Mechanical Engineering by Walid Ibrahim Mazyan entitled, "Numerical Simulations of Drag-Reducing Devices for Ground Vehicles," submitted in January 2013. Thesis advisor is Dr. Essam Wahba. Available are both soft and hard copies of the thesis.